Handling a firearm: State of the art and perspectives applied in psychological evaluation (Research, Society and Development, 2021)
Violence has been part of the history of most places in the world today and Brazil follows the same trend. This reality makes some people try to arm themselves because they feel insecure and look for the firearm as a form of protection. The legislation that regulates the area of weaponry has come over the years seeking greater control, however from 2019 it is possible to perceive an opening and some incentive to the use of firearms. And although the position on possessing a weapon as a means of guaranteeing security brings diverging opinions, this fact has contributed to the increase in demand for registration and carrying a firearm in Brazil. Among the most common compulsory psychological evaluations carried out in Brazil is the psychological evaluation of the possession of a weapon, the purpose of which is to verify whether the person possesses compatible characteristics for armed work or possession and handling of a firearm. However, the area still presents many weaknesses such as: studies in the area are still scarce, non-existence of instruments suggested by the Normative Instruction of the Federal Police nº 78/2014 to evaluate certain psychological constructs, qualification of professionals for application, correction and analysis of results, elaboration of documents, remuneration and devolutive interview to the candidate. It is necessary that the professional is properly trained, updated and act within the ethical precepts listed by the regulations of the area so that their conclusions are scientifically based and bring security to their professional practice.